Effect of Be content on some characteristics of Cu-Al-Be shape memory alloys - Balo, SN; Ceylan, M (Elsevier Science Sa, 2002)
Two kinds of shape memory alloys with the composition Cu-11.6 wt.%Al-0.42 wt.%Be and Cu-11.8 wt.%Al-0.47 wt.%Be were investigated. The structure of some part of sample I and the whole of sample 4 of the alloy with 0.47 wt.%Be content was determined as austerritic DO3 superlattice and the structure of the alloy with 0.42 wt.%Be content was determined as 18R martensitic phase by using X-ray diffraction techniques. From the differential scanning calorimeter (DSC) measurements and microscopic observations, the suitable heat treatment stages for the shape memory characteristics of these two alloys were determined as: annealing at 650 degreesC for 15 min aging at 97 degreesC for 5 min and cooling in water at room temperature. Samples of these two alloys having other heat treatment stages did not show any shape memory properties in the -50 to +200 degreesC temperature range. The difference in the Be contents of these alloys is 0.05 wt.%Be. It has largely affected the transformation temperatures and the A(s) (austenitic phase starting temperature), A(max) (maximum phase transformation rate temperature) and A(f). (austenitic phase finish temperature) temperatures for sample 4 of alloy having 0.47 wt.%Be content were found to be -21.5, -13.1 and 2.2 degreesC, respectively. The A(s), A(max) and A(f) temperatures for sample 6 of alloy having 0.42 wt.%Be were found to be 99, 115 and 146 degreesC, respectively. The A,, A,, and At temperatures for sample 8 of alloy having 0.42 wt.%Be were also found to be 60.8, 77.0 and 93.0 degreesC, respectively. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: differential scanning calorimeter; X-ray diffraction; austenitic-martensitic transformation; shape memory properties